2014
DOI: 10.1007/s12257-014-0830-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of 3,6-anhydro-L-galactose dehydrogenases belonging to the aldehyde dehydrogenase superfamily from marine and soil microorganisms

Abstract: The complete hydrolysis of agarose produces its monomeric sugars, D-galactose and 3,6-anhydro-Lgalactose (L-AnG). Although enzymes of D-galactose metabolism are well characterized, those involved in L-AnG metabolism have not yet been investigated. In this study, we report the identification and characterization of L-AnG dehydrogenase (L-AnGDH), an aldehyde dehydrogenase (ALDH), catalyzing the first step of L-AnG degradation. To compare substrate and cofactor specificities of L-AnGDH, two L-AnGDH genes obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…In summary, bioinformatics analysis and experimental data on L-AnGDH and L-AnGACI from P. marina M091 [1][2][3] clearly showed that the reaction products of LAnGDH and L-AnGACI are L-form metabolites (Fig. 1A).…”
Section: Previous Studies On L-angdh and L-angacimentioning
confidence: 90%
See 4 more Smart Citations
“…In summary, bioinformatics analysis and experimental data on L-AnGDH and L-AnGACI from P. marina M091 [1][2][3] clearly showed that the reaction products of LAnGDH and L-AnGACI are L-form metabolites (Fig. 1A).…”
Section: Previous Studies On L-angdh and L-angacimentioning
confidence: 90%
“…Recently, the 3,6-anhydro-L-galactose dehydrogenase (LAnGDH) [2] and 3,6-anhydro-L-galactonate cycloisomerase (L-AnGACI) [3] from Postechiella marina M091 have been characterized. P. marina M091, which was isolated from a seawater sample obtained at Damupo beach in Pohang, Korea, is a novel agar-degrading microorganism belonging to a new genus within the family Flavobacteriaceae [9].…”
Section: Previous Studies On L-angdh and L-angacimentioning
confidence: 99%
See 3 more Smart Citations